Diaspora Komunitas Tamil di Sumatera Utara: Antara Menjadi India atau Indonesia - Suryo Adi Sahfutra (LPPM Universitas Jambi, 2021)
Cultural sustainability refers to inter-and intra-generation access to cultural heritage. The sustainability of non-material culture is complex because it is related to the experiences of cultural groups and is built by actors in their daily lives. Cultural sustainability is important for the diaspora community because it is an attempt to maintain their cultural identity in their communities while not completely losing contact with cultural elements in their ancestral lands. This paper discusses the strategies used by Muslim Tamils ​​in Medan, North Sumatra, The Muslim Tamils ​​in Indonesia use mainly informal strategies in the process of preserving culture. However, technological advances that have increased the ease of travel and communication have also enhanced the communication and closeness of these two communities with other Tamil communities around the world and have helped further the sustainability of art, language, culinary and religious practices. Muslim Tamils ​​in Medan are experiencing a crisis of identity as Tamils ​​because they are Muslim and many cultural identities conflict with Islamic teachings. Cross-ethnic marriage, assimilation with the non-Tamil community is strong enough to influence changes in cultural orientation, the identity that is still embedded in the Tamil Muslim community can only be found in weddings, culinary and some cultural adaptation practices. At the same time, as citizens of descent, they face the construction of a citizenship identity, becoming Tamils ​​who live in Indonesia or become Indonesians as ethnic Tamils.